ANALYSIS OF THE INFLUENCE OF REVIEWS AND RATINGS OF FASHION 99K OUTLET PRODUCTS ON CONSUMER PURCHASING DECISIONS ON SHOPEE - Monica Carissa Euginia; Vidya Kusumawardani (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of product reviews and ratings on consumer purchase decisions on the Shopee platform, focusing on fashion products from the 99K Outlet store. The increase in online shopping activities makes reviews and ratings an important factor in shaping consumer trust and perception. This study uses a quantitative approach with a survey method of 100 respondents who have shopped at 99K Outlets. Data was collected through a Likert scale online questionnaire and analyzed using SmartPLS 4. The theoretical frameworks used include the Elaboration Likelihood Model (ELM), e-WOM, and social proof to understand how consumers process information from reviews and ratings. The results of the study show that reviews and ratings have a positive and significant effect on purchasing decisions. Informative reviews and high ratings encourage consumers to process information through both central and peripheral channels, in accordance with the ELM approach. In addition, the positive shopping experiences that consumers have experienced have also been proven to strengthen purchasing decisions, especially in the context of repurchases. These findings provide practical contributions for business actors in developing digital marketing communication strategies based on reviews, ratings, and customer experience to increase trust and loyalty on e-commerce platforms.